First record of Sebekia oxycephala (Pentastomida: Sebekidae) infecting Helicops angulatus (Reptilia: Colubridae) in Northeast Brazil - Oliveira, M. C.; Ferreira-Silva, C. [UNESP]; Silva, R. J. [UNESP]; Almeida, W. O.; França, F. G.R.; Lourenço-De-moraes, R. (FapUNIFESP (SciELO), 2023)
In this study, we investigated the infection by pulmonary parasites in the water snake Helicops angulatus. We found four nymphs of the pentastomide parasite Sebekia oxycephala, parasitizing two adult females H. angulatus collected in the municipality of Rio Tinto, Paraíba, Brazil. This occurrence is likely due to the nymphs of this parasite directly infecting aquatic intermediate hosts, such as fish. The result of this study represents the first record of pentastomid infecting H. angulatus.
Primeiro registro de Sebekia oxycephala (Pentastomida: Sebekidae) infectando Helicops angulatus (Reptilia: Colubridae) no Nordeste do Brasil
Keywords: neotropical; parasite; pentastomids; snake